2005
DOI: 10.3732/ajb.92.11.1797
|View full text |Cite
|
Sign up to set email alerts
|

Sexual reproduction, hybridization, apomixis, and polyploidization in the genus Boechera (Brassicaceae)

Abstract: Of the 340 genera in the Brassicaceae, apomictic reproduction is found only in the North American genus Boechera. We investigated phylogenetic relationships, ability to hybridize, mating system, and ploidy levels of 92 lines sampled from 85 populations and representing 19 Boechera species. Phylogenetic analyses based on chloroplast DNA sequences identified three lineages in the genus. Reciprocal crosses of each line were made to a common sexual diploid B. stricta tester. The resulting F(1) progeny were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
192
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(199 citation statements)
references
References 57 publications
4
192
0
3
Order By: Relevance
“…These results demonstrated that (i) some taxa that were previously classified as purely sexual [e.g., B. stricta (48) and B. crandallii (49)] are likely to contain apomicts ( Fig. 1A and Table S1) and (ii) taxa formerly considered as purely apomictic [e.g., B. divaricarpa (37,48)] are likely to be characterized by both sexual and apomictic members (Fig. 1A and Table S1).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…These results demonstrated that (i) some taxa that were previously classified as purely sexual [e.g., B. stricta (48) and B. crandallii (49)] are likely to contain apomicts ( Fig. 1A and Table S1) and (ii) taxa formerly considered as purely apomictic [e.g., B. divaricarpa (37,48)] are likely to be characterized by both sexual and apomictic members (Fig. 1A and Table S1).…”
Section: Discussionmentioning
confidence: 67%
“…Introgression of apomixis alleles from apomictic diploids into different diploid sexual genotypes (43,48) may have facilitated the enormous genetic diversity characteristic of apomictic Boechera (Table S4) (see also ref. 43).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We do not address polyploidization in this paper but it is a relatively well understood phenomenon and evidence for multiple rounds of polyploidization in the evolutionary past of A. thaliana has already been documented (Simillion et al 2002;Wendel 2000). Furthermore, polyploidy is known to occur at the tips of the Brassicaceae tree, for example in the genera Arabidopsis and Boechera (Clauss and Koch 2006;Schranz et al 2005). Meanwhile, the importance of transposable elements in genome evolution is also well documented (Bartolome et al 2002;Bennetzen 2000;Biemont and Vieira 2005;Kumar and Bennetzen 1999;Lenoir et al 2005).…”
Section: Mechanisms Of Change In Genome Sizementioning
confidence: 99%